Evaluation of real-time variometric approach and real-time precise point positioning in monitoring dynamic displacement based on high-rate (20 Hz) GPS Observations - Bezcioglu, M.; Yigit, Cemal Ozer; Karadeniz, B.; Dindar, A.A.; El-Mowafy, Ahmed; Avcı, Ö. (SPRINGER HEIDELBERG, 2023)
We present the performance of real-time (RT)-precise point positioning (PPP) and GNSS-based variometric approach for displacement analysis stand-alone engine (VADASE) methods in capturing dynamic motions in real time. To examine the effectiveness of the two RT methods, different cases, including harmonic motions in various frequency and amplitude ranges, two ground motions similar to those experienced during a real earthquake, and step motions, were generated using a shake table. RT-PPP and VADASE results based on global positioning systems (GPS) observations at a 20 Hz sampling rate were compared with results of the linear variable differential transformer (LVDT) sensor and relative positioning (RP) in the frequency and time domains. Frequency-domain outcomes demonstrated that both RT-based techniques can precisely detect dominant frequencies of the tested motions. However, the time domain results showed that the VADASE can capture the dynamic displacements slightly better than the RT-PPP. While the RMSE values of the differences between the RT-PPP technique and the LVDT vary between 2.3 and 11.6 mm, these values ranged from 1.4 to 6.00 mm for the VADASE approach. Results of earthquake simulation and step motion tests indicated that the VADASE provides more accurate and reliable results than the RT-PPP. It was concluded that the RT-PPP and VADASE approaches can significantly contribute to real-time determination of accurate displacement and natural frequencies of engineering structures and seismic waveforms. They have potential benefits for structural health monitoring, earthquake/tsunami early warning systems, and rapid risk assessment applications.